O025 Smart polymer implants as an emerging technology for treating airway collapse in obstructive sleep apnea: proof of concept. (7th October 2021) - Sideris, A; Wallace, G; Lam, M; Kitipornchai, L; Lewis, R; Jones, A; Jeiranikhameneh, A; Beirne, S; Hingley, L; Mackay, S
Abstract: Study objectives: To assess the use of a novel magnetic polymer implant in reversing airway collapse and identify potential anatomical targets for airway implant surgery in an in vivo porcine model. Methods: Target sites of airway collapse were genioglossus muscle, hyoid bone, and middle constrictor muscle. Magnetic polymer implants were sutured to these sites, and external magnetic forces, through magnets with pull forces rated at 102 kg and 294 kg, were applied at the skin. The resultant airway movement was assessed via nasendoscopy. Pharyngeal plexus branches to the middle constrictor muscle were stimulated at 0.5 mA, 1.0 mA, and 2.0 mA and airway movement assessed via nasendoscopy. Results: At the genioglossus muscles, large magnetic forces were required to produce airway movement. At the hyoid bone, anterior movement of the airway was noted when using a 294 kg rated magnet. At the middle constrictor muscle, an anterolateral (or rotatory) pattern of airway movement was noted when using the same magnet. Stimulation of pharyngeal plexus branches to the middle constrictor revealed contraction and increasing rigidity of the lateral walls of the airway as stimulation amplitude increased. The resultant effect was prevention of collapse as opposed to typical airway dilation, a previously unidentified pattern of airway movement. Conclusions: Surgically implanted smart polymers are an emerging technology showing promise in the treatment of airway collapse in obstructive sleep apnea. Future research should investigate their biomechanical role as an adjunct to treatment of airway collapse through nerve stimulation.